Disability training in the genetic counseling curricula: Bridging the gap between genetic counselors and the disability community. Issue 8 (20th May 2014) - Sanborn, Erica; Patterson, Annette R.
<x xml:space="preserve">Abstract</x> Over the past two decades, disability activists, ethicists, and genetic counselors have examined the moral complexities inherent in prenatal genetic counseling and considered whether and in what ways genetic counseling may negatively affect individuals in the disability community. Many have expressed concerns about defining disability in the context of prenatal decision‐making, as the definition presented may influence prenatal choices. In the past few years, publications have begun to explore the responsibility of counselors in presenting a balanced view of disability and have questioned the preparedness of counselors for this duty. Currently, the Accreditation Council for Genetic Counseling (ACGC) only minimally includes disability training in their competencies for genetic counselors, and in their accreditation requirements for training programs. In an attempt to describe current practice, this article details two studies that assess disability training in ABGC‐accredited genetic counseling programs. Results from these studies demonstrate that experience with disability is not required by the majority of programs prior to matriculation. Though most program directors agree on the importance of including disability training in the curriculum, there is wide variability in the amount and types of training students receive. Hours dedicated to disability exposure among programs ranged from 10 to 600 hours. Eighty‐five percent of program directors surveyed agree that skills for addressing disability should be added to the core competencies. Establishing a set of disability competencies would help to ensure that all graduates have the skills necessary to provide patients with an accurate understanding of disability that facilitates informed decision‐making. © 2014 Wiley Periodicals, Inc.